Clinical outcomes of non‐osteogenic, non‐Ewing soft‐tissue sarcoma of bone––experience of the Toronto Sarcoma Program. (16th October 2020) - Veitch, Zachary W.; Fasih, Samir; Griffin, Anthony M.; Al‐Ezzi, Esmail M.; Gupta, Abha A.; Ferguson, Peter C.; Wunder, Jay S.; Abdul Razak, Albiruni R.
Abstract: Non‐osteogenic, non‐Ewing soft‐tissue sarcoma (NONE‐STS) of bone is a rare presentation of primary bone cancers. Optimal treatments and outcomes for this heterogenous group are poorly described. We evaluated the factors associated with long‐term outcomes in patients with this disease. Patients with localized NONE‐STS of bone treated at the Toronto Sarcoma Program from 1987 to 2017 were identified. Clinical characteristics, treatment, and survival information were collected. Kaplan‐Meier (log‐rank) survival estimates from the time of definitive surgery, with uni‐/multivariate analyses (Cox) of sarcoma‐specific survival were performed. A total of 106 patients (60.4% male; median age 46 years) with NONE‐STS of bone were identified. Common histologies included undifferentiated pleomorphic sarcoma [UPS]/malignant fibrous histiocytoma [MFH] (UPS/MFH, 41.5%), leiomyosarcoma (LMS, 20.8%), and fibrosarcoma (FS, 11.3%). Tumors were often high grade (59.4%) and involved the extremities (88.7%), with most receiving chemotherapy (67.9%) with cisplatin/doxorubicin‐based regimens (73.6%). In the full cohort, 10‐year DFS (45.7%, [95%CI: 35.7‐55.8%]), OS (53.4%, [95%CI: 41.7‐62.2%]), and SSS (63.9%, [95%CI: 53.9‐72.5%]) were moderate. Histology specific, 10‐year SSS was 70.7% [95%CI: 56.1‐85.5%] for UPS/MFH, 51.8% [95%CI: 29.8‐73.8%] for LMS, and 72.2% [95%CI: 45.1‐99.2%] for FS. Only UPS/MFH (n = 4) showed sarcoma‐related death >10 years. Multivariate analysis identified axial location (HR = 35.5, [95%CI: 3.4‐369.6]), high grade (HR = 16.9, [95%CI: 1.6‐185.1]), and disease relapse (HR = 485.1, [95%CI: 36.3‐6482.6]) as risk factors for death ( p  < 0.05). Treatment with chemotherapy (HR = 0.1, [95%CI: 0.01‐0.86]) and necrosis ≥85% (HR = 0.2, [95%CI: 0.04‐0.99]) showed improved survival ( p  < 0.05). NONE‐STS of bone has favorable long‐term survival similar to osteosarcoma. Patients receiving chemotherapy derive benefit in retrospective analyses. UPS/MFH histologies show sarcoma‐related death beyond 10 years. Further data on histologic subgroups are needed. Abstract : In patients with Non‐osteogenic, non‐Ewing soft‐tissue sarcoma (NONE‐STS) of bone, long‐term survival is similar to that of osteosarcoma. Patients receiving chemotherapy who demonstrated ≥85% necrosis on pathologic specimens had improved survival, whereas those with UPS/MFH histology experienced sarcoma‐related death beyond 10 years.